Seven American TODs: Good Practices for Urban Design in Transit-Oriented Development Projects - Justin Jacobson; Ann Forsyth (Journal of Transport and Land Use)
In the past few decades, Transit-Oriented Development (TOD) has emerged as a popular and influential planning concept in the United States. Physical design is an important aspect of making TOD projects work as it is a crucial means of coordinating relatively intensive land uses and multiple transportation modes. This paper analyzes seven American TOD projects in terms of urban design and concludes with a discussion of “good practices” for future TOD projects focusing on development processes, place-making, and facilities. This paper supplements prior scholarship on TOD that has tended to focus on policy issues such as regulation and financing.